Trends of developing auto insurance market in Omsk region - A. A. Demidenko (Вестник СибАДИ, 2017)
The article is devoted to the research of auto insurance market of Omsk region, as a key element of retail insurance. There is presented a characteristic of the condition and existing trends, characterizing the changes of dynamic and structural parameters of auto insurance market’s development, there are marked the occuring problems and there are considered the peculiarities of priority directions of its development in the modern conditions. The particular attention is paid to the compulsory third party auto insurance and Casco. The author has also analyzed the situation regarding insurance companies operating in this market.